The most learned of the Shiʿa: the institution of the Marjaʾi Taqlid - Walbridge, Linda S. (Oxford University Press, 2001)
The problem of who should succeed the Prophet has plagued the Islamic community since the time of his death. The Shiites have decided on a successor, but that does not solve who is the lawful marja (or grand ayatollah) of all the Shi'a